2011
DOI: 10.1097/ccm.0b013e3182190b62
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria-targeted antioxidants protect against mechanical ventilation-induced diaphragm weakness*

Abstract: BACKGROUND Mechanical ventilation (MV) is a life-saving intervention used to provide adequate pulmonary ventilation in patients suffering from respiratory failure. However, prolonged MV is associated with significant diaphragmatic weakness resulting from both myofiber atrophy and contractile dysfunction. Although several signaling pathways contribute to diaphragm weakness during MV, it is established that oxidative stress is required for diaphragmatic weakness to occur. Therefore, identifying the site(s) of MV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

24
289
3
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 227 publications
(321 citation statements)
references
References 36 publications
24
289
3
5
Order By: Relevance
“…Importantly, two independent studies have confirmed that prolonged MV also results in mitochondrial damage in the human diaphragm (80,106). Finally, treatment of animals with a mitochondrialtargeted antioxidant prevents the MV-induced activation of several proteolytic systems and prevents VIDD (82). Together, these findings indicate that ventilator-induced mitochondrial ROS emission is a required upstream signal for protease activation in the diaphragm during prolonged MV.…”
Section: R468supporting
confidence: 51%
See 4 more Smart Citations
“…Importantly, two independent studies have confirmed that prolonged MV also results in mitochondrial damage in the human diaphragm (80,106). Finally, treatment of animals with a mitochondrialtargeted antioxidant prevents the MV-induced activation of several proteolytic systems and prevents VIDD (82). Together, these findings indicate that ventilator-induced mitochondrial ROS emission is a required upstream signal for protease activation in the diaphragm during prolonged MV.…”
Section: R468supporting
confidence: 51%
“…However, because the rat and human diaphragm are anatomically alike and contain a similar fiber type composition (76,81), the rat has become the most commonly used animal model to study MV-induced changes in diaphragm fiber size and function. Several studies reveal that as few as 12 h of controlled MV results in a 10 -15% reduction in the cross-sectional area of all rat diaphragm fiber types (i.e., type I, type IIa, and type IIx/b) (67,69,82,103). This MV-induced rat diaphragmatic fiber atrophy increases as a function of time and approaches a 30% reduction in fiber cross-sectional area following 18 -24 h of prolonged MV (33,100,117).…”
Section: Mv-induced Diaphragm Atrophymentioning
confidence: 99%
See 3 more Smart Citations